The complete photo guide to felting - Lane, Ruth, 1961- (Creative Pub. International, 2012)
"This richly illustrated how-to book is a comprehensive reference for various felting techniques, including needle felting, wet felting, and nuno felting. With these easy-to-follow, step-by-step directions and hundreds of full-color photos, you'll be able to explore these easy projects that provide fun opportunities for you to try the techniques. Galleries of unique felted designs and creations by renowned fabric artists act as beautiful examples and inspiration to pursue the hobby yourself"--